Esenbeckia cowanii (Rutaceae), epitypification and emendation - Dias, Pedro; Udulutsch, Renata Giassi [UNESP]; Pirani, José Rubens (Missouri Botanical Garden Press, 2013)
A complete description of Esenbeckia cowanii Kaastra (Rutaceae) is presented, including new details for floral morphology. The original type of this taxon included only fruiting material, thus we designate an epitype with flowers. In addition, we provide taxonomic emendation to E. cowanii, including its leaf morphology variation, details of the fruit and seed, and an update of its geographic distribution.
Keywords: Brazil; Esenbeckia; Pilocarpinae; Rutaceae